Law Education and Optimalization Community Organizations from the Anarchism Motorcycle Gang in Medan - Yudhistira, Eko; Sinulingga, Tommy Aditia; Al Fajar, Muhammad Din; Kembaren, Mardiah Mawar; Gunaika, Raka (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The presence of motorbike gangs in Indonesia is one of the disturbing forms of juvenile delinquency. Circumstances such as those previously explained have provided a strong impetus to discuss and look for the best alternative solution in overcoming the problems perpetrated by motorcycle gangs. Therefore, it is very important to respond to the problem of methods and actions to deliver a young generation that is responsible and participates in providing real assistance to the nation and state.